If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -2 = -3p + -4n Reorder the terms: -2 + x = -3p + -4n Reorder the terms: -2 + x = -4n + -3p Solving -2 + x = -4n + -3p Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + x = -4n + 2 + -3p Combine like terms: -2 + 2 = 0 0 + x = -4n + 2 + -3p x = -4n + 2 + -3p Reorder the terms: x = 2 + -4n + -3p Simplifying x = 2 + -4n + -3p
| u=-3a+3 | | 6=9/7z | | W^2-24w+23=0 | | 2/3*3.14 | | 2/3*3.14*4*4*4 | | z=3a-1 | | -3y^2-72y=75 | | 6x-12+3=15 | | (5x+4)(7x+3)= | | 3x+7=17-6c | | 5n-7=2n+20 | | -4g^2+40g+116=0 | | 360/x=4 | | 3x+8y=68 | | 2z-z+3z=20 | | 5.6y-17=11 | | 2a(xb+5)+b(2x-4)+2abx+3b= | | 1/t=-1 | | 6x-17=35+4x | | 2v^2+24v-34=0 | | x-90=90-5x | | -44-8x=-5x+28 | | 2x+54=26 | | (-5)(2)(0)(-1)= | | -74-3x=4x+38 | | 3-x^2=5x^2-9 | | -12x-161=-x+48 | | 6+(2+7)=(6+2)+7 | | 4(x-3)=x-12+7x | | (-4*pi*x^2)/(2*pi*x)=0 | | 1.4+x=5.8 | | x-60=-7x+84 |